Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi Di Nagan Raya - Reni Restia; Teuku Zulham; Fajri Hadi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
Abstract This study aims to analyse the effect of macro variables (provincial minimum wages, inflation, economic growth and population) on the unemployment rate in Aceh Province. The type of data used in this study is quantitative time series data from 2000 to 2018 (19 years) about unemployment, provincial minimum wages, inflation, economic growth and population. This research uses multiple linear regression method using the EVIEWS application. The data used in this study were sourced from the Central Statistics Agency (BPS) of Aceh Province. The results showed that partially the provincial minimum wage and inflation had a positive and significant effect on the unemployment rate in Aceh Province and economic growth and population had a positive and not significant effect on the unemployment rate in Aceh Province. While simultaneously (overall) shows that the variable provincial minimum wage, inflation, economic growth and population have a positive and significant effect on the unemployment rate in Aceh Province. Keywords: Provincial Minimum Wage, Inflation, Economic Growth, Population, Unemployment.